ANALISIS KELAYAKAN TARIF PDAM KABUPATEN LOMBOK TIMUR DENGAN PRINSIP FULL COST RECOVERY BERDASARKAN PERMENDAGRI NOMOR 21 TAHUN 2020 - Gina Dwi Septariani Azhar; Animah Animah; Widia Astuti (Jurnal Ilmiah Akuntansi Indonesia, 2022)
The aim of this research is to understand the results of drinking water eligibility using Break Even Point (BEP), Benefit Cost Ratio (BCR) analysis, and new water tariff calculation at Drinking Water Regional Industry (PDAM) Lombok Timur according to the Ministry of the Interior Rule (PERMENDAGRI) Number 21 2020 to achieve Full Cost Recovery principal. This research uses quantitative descriptive method with primary data through interviews and secondary obtained through documentation. The result of this research showed that East Lombok PDAM suffer loss due to water tariff that was not Full Cost Recovery. On Break Even Point (BEP) analysis calculation, it explained that East Lombok PDAM income and amount of water sold are lower than BEP value. Meanwhile, BCR value got 0,95 or less than 1. So, the water tariff at East Lombok PDAM is declared unfeasible based on analysis of break even point and benefit cost ratio. According to that, the way could be taken by East Lombok PDAM is make new tariffs adjustment policy. So, calculations based on PERMENDAGRI Number 21 2022 got new tariffs, which are: basic tariff Rp. 2.979, low tariff Rp. 2.228, and full tariff Rp. 4.082. Those tariffs are higher than previous East Lombok PDAM tariff.